The Pintoe Aceh Motif in Macramé Window Curtains and Tablecloth Products - Irmawati, Irmawati; Naufa, Miftahun; Rahmawati, Rahmawati (V-art: Journal of Fine Art, 2023)
The creation of this work began with the Pintoe Aceh motif, which has gained wide recognition in Aceh, inspired by the natural richness of Aceh, encompassing flora, fauna, and geometric patterns. The Pintoe Aceh motif boasts a high aesthetic appeal, enriched with elements such as Bungoeng Meulu, Oen Paku, Boh Ungkot, and geometric patterns that exude elegance and charm. The artists were compelled to use the Pintoe Aceh motif as the basis for creating window curtains and tablecloths. The primary objective of this creative endeavor is to contribute to the preservation of the Pintoe Aceh motif as a cultural heritage of the Acehnese community while producing a variety of original macramé products. The creative process involves four main stages: pre-design, design, realization, and presentation. The concept adopted embraces the concept of symbolic expression, combining modern art with tradition. This creation has yielded unique macramé products, specifically designed to enhance learning spaces, in the form of window curtains and tablecloths.